Does the combined application of organic and mineral nutrient sources influence maize productivity? a meta analysis - Chivenge, Pauline P.; Vanlauwe, Bernard; Six, Johan (Springer, 2011)
The combined application of organic resources (ORs) and mineral fertilizers is increasingly gaining recognition as a viable approach to address soil fertility decline in sub-Saharan Africa (SSA). We conducted a meta-analysis to provide a comprehensive and quantitative synthesis of conditions under which ORs, N fertilizers, and combined ORs with N fertilizers positively or negatively influence Zea mays (maize) yields, agronomic N use efficiency and soil organic C (SOC) in SSA. Four OR quality classes were assessed; classes I (high quality) and II (intermediate quality) had >2.5% N while classes III (intermediate quality) and IV (low quality) had <2.5% N and classes I and III had <4% polyphenol and <15% lignin. On the average, yield responses over the control were 60%, 84% and 114% following the addition of ORs, N fertilizers and ORs + N fertilizers, respectively. There was a general increase in yield responses with increasing OR quality and OR-N quantity, both when ORs were added alone or with N fertilizers. Surprisingly, greater OR residual effects were observed with high quality ORs and declined with decreasing OR quality. The greater yield responses with ORs + N fertilizers than either resource alone were mostly due to extra N added and not improved N utilization efficiency because negative interactive effects were, most often, observed when combining ORs with N fertilizers. Additionally, their agronomic N use efficiency was not different from sole added ORs but lower than N fertilizers added alone. Nevertheless, positive interactive effects were observed in sandy soils with low quality ORs whereas agronomic use efficiency was greater when smaller quantities of N were added in all soils. Compared to sole added ORs, yield responses for the combined treatment increased with decreasing OR quality and greater yield increases were observed in sandy (68%) than clayey soils (25%). While ORs and ORs + N fertilizer additions increased SOC by at least 12% compared to the control, N fertilizer additions were not different from control suggesting that ORs are needed to increase SOC. Thus, the addition of ORs will likely improve nutrient storage while crop yields are increased and more so for high quality ORs. Furthermore, interactive effects are seldom occurring, but agronomic N use efficiency of ORs + N fertilizers were greater with low quantities of N added, offering potential for increasing crop productivity.